Consolidation of B4C–VB2 eutectic ceramics by spark plasma sintering - Demirskyi, Dmytro (2016)
The in situ synthesis and consolidation of B4C–VB2 eutectic composites by spark plasma sintering (SPS) is reported. The microstructure properties were determined for composites with the B4C–VB2 eutectic composition as functions of the VB2 content and the VB2–VB2 interlamellar spacing. A change of VB2 concentration from 45 to 48 mol.% resulted in the formation of the rod-like eutectic microstructure. Indentation fracture toughness values higher than 4 MPa·m1/2 were identified for eutectic composites with interlamellar spacings between 0.9 and 1.2 µm. The composites obtained by SPS with a composition of 45 mol.% VB2 exhibited a lower Vickers hardness (23–24 GPa) and higher indentation fracture toughness (up to 4.5 MPa·m1/2) than the eutectic composites with 48 mol.% of VB2.